2008
DOI: 10.1016/j.fertnstert.2008.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pelvic pain associated with endometriosis

Abstract: Pain associated with endometriosis requires careful evaluation to exclude other potential causes and may involve a number of different mechanisms. Both medical and surgical treatments for pain related to endometriosis are effective and choice of treatment must be individualized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 82 publications
0
40
0
3
Order By: Relevance
“…Combined oral contraceptives, while widely used to manage symptoms of endometriosis, are not approved for this indication in most countries and their use is largely unsupported by solid clinical trial evidence [4]. One study has demonstrated that the use of a low-dose oral contraceptive pill is an effective treatment for dysmenorrhea associated with endometriosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Combined oral contraceptives, while widely used to manage symptoms of endometriosis, are not approved for this indication in most countries and their use is largely unsupported by solid clinical trial evidence [4]. One study has demonstrated that the use of a low-dose oral contraceptive pill is an effective treatment for dysmenorrhea associated with endometriosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Women suffering from endometriosis may be treated with oral contraceptives or in severe cases by hysterectomy, which have both been observed in other studies to be associated with increased risk of PD 7,37. Further study, including prescription and treatment information, would be warranted for these findings.…”
Section: Discussionmentioning
confidence: 79%
“…Препаратом первой линии для долговремен-ного лечения болевого синдрома при эндометриозе можно считать диеногест 2 мг. Согласно рекоменда-циям SOGC Clinical Practice Guideline [1,7,8,10,27,28,30,31], монотерапия прогестинами внутрь отно-сится к первой линии терапии, а терапия а-ГнРГ в комбинации с заместительной гормональной тера-пией в качестве возвратной терапии является тера-пией второй линии.…”
Section: выводыunclassified